2009
DOI: 10.1007/s00228-009-0734-4
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of anthracyclines in vitro and in vivo in acute myeloid leukemia cells in relation to apoptosis and clinical response

Abstract: Aims To study anthracycline-induced apoptosis in leukemic cells isolated from patients with acute myelogenous leukemia (AML) in vitro and to compare intracellular anthracycline concentrations causing apoptosis in vitro with those obtained in vivo during anthracycline treatment. Methods Mononuclear blood cells from AML patients were isolated before (n=20) and after anthracycline infusion (n= 24). The pre-treated cells were incubated in vitro with daunorubicin (DNR) and/or idarubicin (IDA). Anthracycline concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
2
7
0
3
Order By: Relevance
“…IDA is a synthetic analog of DNR and one of the most effective inhibitors of DNA topoisomerase. Alex et al found a significant relation between apoptosis induction in leukemic cells by IDA in vitro and the disease remission measured by the percent of residual leukemic cells in bone marrow [29]. In this study, we found the sequential combination treatment of DAC and IDA efficiently inhibited the formation of AML cell clones and tumor growth in a subcutaneous AML mouse model.…”
Section: Discussionsupporting
confidence: 59%
“…IDA is a synthetic analog of DNR and one of the most effective inhibitors of DNA topoisomerase. Alex et al found a significant relation between apoptosis induction in leukemic cells by IDA in vitro and the disease remission measured by the percent of residual leukemic cells in bone marrow [29]. In this study, we found the sequential combination treatment of DAC and IDA efficiently inhibited the formation of AML cell clones and tumor growth in a subcutaneous AML mouse model.…”
Section: Discussionsupporting
confidence: 59%
“…After proving the favourable toxicity profile of investigated compounds there have been attempts to determine the ability of derivatives to induce apoptosis. Apoptosis plays an important role in the cytotoxic activity of first-and second-generation anthracyclines in the therapy of solid cancer [52] and leukaemia [53]. There are reports describing the role of DOX in the generation of morphological alterations in the nuclei [54,55].…”
Section: Formamidine Derivatives Of Doxorubicinmentioning
confidence: 98%
“…Hence, attenuation of CBR1 activity using pharmacologic inhibitors could improve the therapeutic response to DAUN and DOX and reduce the side effects in patients undergoing chemotherapy [45,95,96,101]. Additionally, CBR1 may be implicated in the large interpatient variabilities in the pharmacokinetics of both DAUN and DOX [105][106][107]. The reasons for these interindividual variabilities in DAUN and DOX pharmacokinetics remain unclear [45,105], and the consequences of such differences in pharmacokinetics are unpredictable with regard to toxicity and outcome of therapy [45,108].…”
Section: Anti-cancer Drugsmentioning
confidence: 98%